2009
DOI: 10.5944/rppc.vol.14.num.3.2009.4077
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes y conductas sexuales de riesgo para la infección por VIH/SIDA en jóvenesespañoles

Abstract: Resumen: En este estudio se analizan las actitudes y conductas sexuales de riesgo de los jóvenes españoles respecto a la infección por VIH. Se administró el Cuestionario de Prevención del SIDA a 196 jóvenes. Los resultados muestran lagunas importantes en la información (sólo el 59% sabe que el sexo oral sin preservativo es una práctica de riesgo); el uso sistemático del preservativo es moderado en el coito (indican haberlo utilizado en el 53% de las relaciones del mes anterior); y muy bajo en las relaciones or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
2
16
0
3
Order By: Relevance
“…The profile of people who did not know their HIV status before diagnosis were patients younger than 25 years or those older than 44 years and who had heterosexual sex (7,8) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Numerous studies developed in Spain have shown a high frequency of sexual risk behaviors among young heterosexuals and homosexuals (9)(10)(11)(12)(13)(14)(15), but few studies have examined the frequency of HIV antibody testing and determinants of delayed diagnosis (16). According to the Survey on Health and Sexual Habits conducted by the National Statistics Institute, only 10.4 % of the population in Spain has been tested voluntarily to find out their HIV status (17).…”
mentioning
confidence: 99%
“…The profile of people who did not know their HIV status before diagnosis were patients younger than 25 years or those older than 44 years and who had heterosexual sex (7,8) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Numerous studies developed in Spain have shown a high frequency of sexual risk behaviors among young heterosexuals and homosexuals (9)(10)(11)(12)(13)(14)(15), but few studies have examined the frequency of HIV antibody testing and determinants of delayed diagnosis (16). According to the Survey on Health and Sexual Habits conducted by the National Statistics Institute, only 10.4 % of the population in Spain has been tested voluntarily to find out their HIV status (17).…”
mentioning
confidence: 99%
“…It seems logical to think that there is greater probability of steady relationships; therefore people could use other contraceptives methods that do not prevent STIs. Different studies in Spain suggest the existence of the phenomenon called monogamy not protective [2][3][4][5]. They reported about negative beliefs that arise when using a condom with a steady partner (e.g., mistrustfulness, lack of love for the other person).…”
Section: Discussionmentioning
confidence: 99%
“…The unprotected sex put at risk for HIV infection, other sexually transmitted infections (STIs) and unwanted pregnancy [2][3][4][5]. Furthermore, safe sexual behavior (for example, abstinence, consistent condom use or mutual monogamy with an HIV-negative partner) is the only way to prevent sexual transmission of HIV and STIs.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, si bien las mujeres mejoran en la variable «sexo seguro» en distintas situaciones, los hombres muestran una evolución más positiva en la misma. Este resultado, confirma investigaciones previas en las que los hombres han revelado cambios más consistentes en las variables conductuales (Ballester et al, 2009).…”
Section: Sexo Segurounclassified